The incidence of polyspermy during in vitro fertilisation. A study at the H. F. Verwoerd Hospital, Pretoria - Sevenster, C B; van der Merwe, J V; van Zyl, C (South African medical journal, 1987)
Results from 1249 in vitro-fertilised human oocytes were analysed to identify the incidence of polyspermy. In this study polyspermy occurred in 23 oocytes (1.8%). The effects of the various ovulation induction protocols employed, maturation of oocytes, incubation time before insemination and anaesthesia exposure were examined in order to identify a cause for polyspermy. Early diagnosis of polyspermy is important because the polyspermic embryo may appear morphologically normal at a later stage but should not be transferred since this nearly always results in a spontaneous abortion.